MyUniNet : its contribution in resource sharing and library networking in Malaysia - Samsuddin, Samsul Farid; Kaspol, Muizzudin (2012)
Persidangan Perpustakaan Universiti dan Perpustakaan Negara Malaysia(PERPUN) is a forum of cooperation among the Heads of public universities and government-linked universities and the Director General, National Library of Malaysia. Malaysian University Libraries & National Library Network (MyUniNet) is the official name for PERPUN portal which is accessible at http://perpun.upm.edu.mvl. MyUniNet portal symbolises the cooperation and smart partnership between PERPUN members. The development of the portal illustrates the commitment of PERPUN in providing scholarly information resources via a single access. The portal offers access to MyTO which lists the theses collection in all public and selected private university libraries and MyULIS which lists titles of all serial publications subscribed by the libraries. MyULIS is one of the reference sources to get information and materials through interlibrary loan services (ILL). PERPUN has moved a step forward by providing services in digital resources and content. The purpose of this paper is to describe the initiatives talcen by all university libraries in expanding and optimizing the use of digital resources and content in research, and resource sharing among the universities. The data for this study will be collected through questionnaire, interviews and author's personal experiences and observations. The study will also focus on the role of two Special Interest Groups; Malaysian Information System Librarians (MySyL) and Malaysian Online E-Resources Consortium (MOLEC) in the development and the implementation of MyUniNet Portal.